Balanced transcription of cell division genes in Bacillus subtilis as revealed by single cell analysis. (24th May 2013) - Trip, Erik Nico; Veening, Jan‐Willem; Stewart, Eric J.; Errington, Jeff; Scheffers, Dirk‐Jan; Vicente, Miguel; Ayala, Juan; Daley, Daniel
Summary Cell division in bacteria is carried out by a set of conserved proteins that all have to function at the correct place and time. A cell cycle‐dependent transcriptional programme drives cell division in bacteria such as Caulobacter crescentus. Whether such a programme exists in the Gram‐positive model organism Bacillus subtilis is unknown. Here, we investigate the role of gene transcription as a potential regulatory mechanism for control of division in B. subtilis. Transcriptional GFP fusions in combination with flow cytometry demonstrated a constitutive promoter activity, independent of growth rate, of nine tested cell division genes. These measurements were verified by quantitative real‐time reverse‐transcription PCR (qrtPCR). Time‐lapse fluorescence microscopy was performed on a set of selected reporter strains to test transcriptional regulation during the cell cycle. Interestingly, although the average fluorescence remained constant during cell‐cycle progression, individual cells demonstrated a roughly twofold higher promoter activity at the end of the cell cycle. This cell cycle‐dependent increased promoter activity can be partly explained by the doubled promoter copy number after DNA replication. Our results indicate that the transcriptional activity of promoters for cell division genes remains constant regardless of growth rate and cell‐cycle state, suggesting that regulation of cell division in B. subtilis predominantly takes place at the post‐translational level.